KOMUNIKASI POLITIK AFRIZAL SINTONG-H. SULAIMAN PADA PEMILIHAN KEPALA DAERAH KABUPATEN ROKAN HILIR TAHUN 2020 - Safii, M.; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The presence of a partner with the AMAN jargon is an attraction in itself compared to other couples. This is Afrizal Sintong-H. Sulaiman is an energetic young couple from another couple, and it is certain that his energetic young spirit builds a more advanced Rokan Hilir. This study aims to determine political communication and use of media campaigns by Afrizal Sintong-H. Sulaiman in the 2020 election for the Regional Head of Rokan Hilir Regency. This research is a descriptive qualitative research using data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman models. The results of the study stated that the communicators were the Regent and Deputy Regent, the Community Success Team (parents) and the Community (millennials). The results of this study indicate that the political communication of Afrizal Sintong-H. Sulaiman in the 2020 election for the Regional Head of Rokan Hilir Regency; Use verbal and nonverbal communication. The media used are face-to-face media, social media, external media and small format media. Keywords: Political Communication, Communication Style, Media Campaign